Spontaneous rupture of the esophagus: report of two cases - Ali Said Esgaib; Carlos Joji Ima Eda; Rogério lgnácio de Oliveira; Mário Cláudio Ghefter; Roberto de Menezes Lyra; Ruggero Bernardo Guidugli; Nilson Roberto Ribeiro de Oliveira Jr. (São Paulo Medical Journal)
OBJECTIVE - To study the diagnosis, prognosis and management of spontaneous rupture of the esophagus. DESIGN: This is a retrospective study through the analysis of two cases with delayed diagnosis and subsequent treatment at the Track Surgery Service. LOCALE: The study was performed at the Thoracic Surgery Unit of the Hospital do Servidor Público Estadual Francisco Morato de Oliveira in the city of São Paulo. This is a specialized service. PARTICIPANTS: The two patients reported on had suffered spontaneous rupture of the esophagus. They were transferred to the Thoracic Surgery Unit because of the worsening of their condition in the previous institution which they had been admitted into. MEASUREMENT: The two patients with esophagus pleural fistula received similar treatment, initially advocated by Kanashin in Russia and Hauer-Santos in the United States, which consists of washing the fistula and using continuous pleural aspiration. RESULTS: Although both patients had to spend a long period of time in hospital, their evolution was satisfactory with the treatment adopted, and the fistula closed. CONCLUSION: The authors conclude that the method of lavage of the mediastinum and continuous pleural aspiration, in patients who after spontaneous rupture of the esophagus developed a pleural esophagus fistula due to belated diagnosis, is an alternative and satisfactory therapy. Furthermore, in order to have the best outcome, an early diagnosis is recommended and thoracostomy as the surgical procedure, with primary suture.